2015
DOI: 10.1080/17458080.2015.1059504
|View full text |Cite
|
Sign up to set email alerts
|

Green synthesis of zinc oxide nanoparticles using tomato(Lycopersicon esculentum)extract and its photovoltaic application

Abstract: With an increasing awareness of green and clean energy, zinc oxide-based solar cells were found to be suitable candidates for cost-effective and environmentally friendly energy conversion devices. In this paper, we have reported the green synthesis of zinc oxide nanoparticles (ZnONPs) by thermal method and under microwave irradiation using the aqueous extract of tomatoes as non-toxic and ecofriendly reducing material. The synthesised ZnONPs were characterised by UVÀvisible spectroscopy (UVÀvis), infra-red spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
28
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 107 publications
(34 citation statements)
references
References 25 publications
(9 reference statements)
5
28
0
1
Order By: Relevance
“…while, Joel reported that chemically fabricated zinc oxide nanoparticles were commonly white and the greensynthesized nanoparticles were brown in color (Joel.C & Badhusha, 2016). The results of existing studies indicate that zinc oxide nanoparticles often have adsorption peaks between 305-375 nm (Dhanemozhi, Rajeswari, & Sathyajothi, 2017;Senthilkumar & Sivakumar, 2014;Sutradhar & Saha, 2016;Yedurkar, Maurya, & Mahanwar, 2016). The 330 nm absorption peak obtained in this study is in complete agreement with the previously published works.…”
Section: Discussionsupporting
confidence: 91%
“…while, Joel reported that chemically fabricated zinc oxide nanoparticles were commonly white and the greensynthesized nanoparticles were brown in color (Joel.C & Badhusha, 2016). The results of existing studies indicate that zinc oxide nanoparticles often have adsorption peaks between 305-375 nm (Dhanemozhi, Rajeswari, & Sathyajothi, 2017;Senthilkumar & Sivakumar, 2014;Sutradhar & Saha, 2016;Yedurkar, Maurya, & Mahanwar, 2016). The 330 nm absorption peak obtained in this study is in complete agreement with the previously published works.…”
Section: Discussionsupporting
confidence: 91%
“…They proved that green NPs showed enhanced performance compared to chemical ZnO NPs. There have been several similar works on the synthesis of ZnO NPs via green methods . In most of these methods, the researchers tended to use natural compounds (such as gelatin, C. citriodora and Aloe) or water‐soluble chemicals; therefore, these procedures can be considered as an environmental threat.…”
Section: Introductionmentioning
confidence: 99%
“…However, during the enlarged syntheses, reproducibility is critically important for the potential technological applications of GQDs. In continuation of our research work [27][28][29], in this work we have reported that the pyrolysis of citric acid was carried out which on further addition of sodium hydroxide for maintaining the pH produced GQDs. The effect of different pH on the formation of GQDs was studied in detail.…”
Section: Introductionmentioning
confidence: 99%